Camera Trap-Based Assessment of Wild Boar (Sus scrofa) Abundance in a Tropical Protected Forest Landscape of Sumatra - Sau San Lu’luah; Dian Iswandaru; Aris Hidayat; Bainah Sari Dewi (Forest and Nature, 2025)
Wild boar (Sus scrofa) plays a crucial role in tropical forest ecosystems but also poses ecological and socio-economic challenges, including crop damage and susceptibility to African swine fever (ASF). This study assessed temporal changes in the relative abundance of wild boars in the core block of the Batutegi Protected Forest Management Unit (KPHL Batutegi), Lampung Province, Indonesia, using camera trap data collected in 2018, 2022, and 2024. A total of 18 camera traps were installed at fixed monitoring points, and all photographs of wild boars were processed to determine independent events (IE) following a ≥ 30-minute interval rule; these IE data were then used to calculate the Relative Abundance Index (RAI). The results revealed substantial temporal fluctuations: RAI was 3.18 in 2018, declined drastically to 0.55 in 2022, likely due to ASF outbreaks, and increased significantly to 7.29 in 2024, indicating potential recovery or adaptation to post-outbreak conditions. Seasonal patterns showed higher activity during drier months, suggesting that rainfall influences foraging behavior and the detectability of animals. Beyond wild boars, camera traps also recorded diverse non-target wildlife, including several threatened species listed in the International Union for Conservation of Nature (IUCN) Red List, emphasizing the ecological significance of the Batutegi Protected Forest. These findings highlight the importance of long-term wildlife monitoring using camera traps to detect population fluctuations, evaluate disease impacts, and inform adaptive management strategies. Continuous observation is essential for balancing wildlife conservation and mitigating human–wildlife conflict in tropical protected forests.